Modeling the earth for oil exploration : final report of the CEC's Geoscience I Program, 1990-1993 - Helbig, Klaus (Pergamon : Elsevier Science, 1994)
This volume presents an overview of the results of a European Union integrated program in which approximately two hundred earth scientists participated, drawn from all fields related to exploration. Two classes of modeling were addressed - geological modeling - the relationship between the conditions of sedimentation and the resulting reservoir conditions; and wave-propagation modeling - the investigation of wave-propagation through media of various degrees of complexity. Wave-propagation modeling was carried out either mathematically or physically with the most modern tools. An important aspe.